Randomized comparison of cardiotoxicity with 60 versus 90 mg daunorubicin in AML induction therapy - Dendorfer, Stefan Markus; Schmidt-Brücken, Katharina; Kramer, Michael; Steffen, Björn; Schliemann, Christoph; Mikesch, Jan-Henrik; Alakel, Nael; Herbst, Regina; Hänel, Mathias; Hanoun, Maher; Kaufmann, Martin; Weinbergerova, Barbora; et al. (American journal of hematology, 2026)
Anthracyclines are an essential component of induction therapy for acute myeloid leukemia (AML), but their optimal dosing and the associated risk for cardiotoxicity remain under debate. The DaunoDouble trial compared daunorubicin at 60 (Dauno60) versus 90 mg/m2 (Dauno90) in combination with cytarabine (100 mg/m2 for 7 days) in newly diagnosed AML patients aged 18-65 years. Cardiac function was assessed by left ventricular ejection fraction (LVEF) and cardiac biomarkers (high-sensitivity troponin T [hsTnT], NT-proBNP) before treatment and on Day 15 in 317 randomized patients. Median LVEF declined significantly from 65% [IQR 60%-68.5%] to 61% [IQR 58%-67.8%] across all patients (p < 0.01), without significant differences between treatment arms. NT-proBNP levels measured after induction therapy correlated negatively with LVEF at the same time point (ρ = −0.24, p = 0.02), but did not change significantly during induction—neither between Day 1 and 15 nor between treatment arms. HsTnT levels increased significantly from 5 [IQR 4-8] to 8 ng/L [IQR 6-14] across all patients (p < 0.01), with higher post-induction values in the Dauno90 group (9.5 ng/L [IQR 7-14]) compared to Dauno60 (7 ng/L [IQR 5-14]; p < 0.01). In exploratory subgroup analyses, post-induction hsTnT levels were also significantly higher in patients with obesity and arterial hypertension. These findings provide evidence of a dose-dependent cardiotoxic effect of daunorubicin, already apparent at standard induction doses, and underscore the importance of early cardiac monitoring. Long-term follow-up will be essential to determine the clinical significance of these early changes. Trial Registration: ClinicalTrials.gov identifier: NCT02140242